If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40x = 39(x + 45) Reorder the terms: 40x = 39(45 + x) 40x = (45 * 39 + x * 39) 40x = (1755 + 39x) Solving 40x = 1755 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. 40x + -39x = 1755 + 39x + -39x Combine like terms: 40x + -39x = 1x 1x = 1755 + 39x + -39x Combine like terms: 39x + -39x = 0 1x = 1755 + 0 1x = 1755 Divide each side by '1'. x = 1755 Simplifying x = 1755
| (5X-2)+2x=8 | | X/-15=4 | | 5x+4=.25 | | Ix+cI=C | | 0.7(8x+16)=1.6-(x+2) | | (2-X)+5=7 | | 9x/(7x-14) | | 2x-4x+3x-4+5x= | | a^2-22a+185=0 | | 3/2(20)-4 | | Xsquared-6x=6 | | 2w+3=4w+-5 | | 3+2q-(4q+9)-(5q+6)= | | 6(x+3)-3(x+2)=27 | | 57-(5x+4)=5(x+4)+x | | 24=16tsquared | | 26x-8-16x+2=26x-4-16x+17 | | 6(2+4y)=2y+4y+8y | | 3.5(1)=3.5 | | x/0.9=7.2 | | (72y^3)/(64y^7) | | ((x)/(0.01-x)(0.02-x))=0.45 | | 10p+56=176-p | | (72y^3/64y^7) | | b/6=-28 | | (3x/5)-7=(2x/6)+1 | | 72y^3/64y^7 | | a-3.95=1.5 | | 55=(9-d)11 | | 4+7y=10 | | mx^2-(m-3)x+4m=0 | | -19+x=x+22 |